Development of flow cytogenetics and physical genome mapping in chickpea (Cicer arietinum L.) - Vlácilová, K; Ohri, D; Vrána, J; Cíhalíková, J; Kubaláková, M; Kahl, G; Dolezel, J (Chromosome research, 2002)
Procedures for flow cytometric analysis and sorting of mitotic chromosomes (flow cytogenetics) have been developed for chickpea (Cicer arietinum). Suspensions of intact chromosomes were prepared from root tips treated to achieve a high degree of metaphase synchrony. The optimal protocol consisted of a treatment of roots with 2 mmol/L hydroxyurea for 18 h, a 4.5-h recovery in hydroxyurea-free medium, 2 h incubation with 10 micromol/L oryzalin, and ice-water treatment overnight. This procedure resulted in an average metaphase index of 47%. Synchronized root tips were fixed in 2% formaldehyde for 20 min, and chromosome suspensions prepared by mechanical homogenization of fixed root tips. More than 4 x 10(5) morphologically intact chromosomes could be isolated from 15 root tips. Flow cytometric analysis of DAPI-stained chromosomes resulted in histograms of relative fluorescence intensity (flow karyotypes) containing eight peaks, representing individual chromosomes and/or groups of chromosomes with a similar relative DNA content. Five peaks could be assigned to individual chromosomes (A, B, C, G, H). The parity of sorted chromosome fractions was high, and chromosomes B and H could be sorted with 100% purity. PCR on flow-sorted chromosome fractions with primers for sequence-tagged microsatellite site (STMS) markers permitted assignment of the genetic linkage group LG8 to the smallest chickpea chromosome H. This study extends the number of legume species for which flow cytogenetics is available, and demonstrates the potential of flow cytogenetics for genome mapping in chickpea.
Keywords: Cytogenetics; fyzikální mapování chromozomů; polymerázová řetězová reakce; Genome, Plant; genom rostlinný; karyotypizace; hybridizace in situ fluorescenční; Metaphase; mikrosatelitní repetice; indoly; Plant Roots; Karyotyping; Mitosis; Sequence Tagged Sites; chromozomy rostlin; Flow Cytometry; Chromosomes, Plant; Genetic Linkage; kořeny rostlin; cytogenetika; DNA rostlinná; místa se sekvenční adresou; DNA, Plant; Microsatellite Repeats; Physical Chromosome Mapping; průtoková cytometrie; genetická vazba; Cicer; Indoles; Cell Cycle; metafáze; In Situ Hybridization, Fluorescence; Polymerase Chain Reaction; mitóza; buněčný cyklus